2015
DOI: 10.1128/aac.00197-15
|View full text |Cite
|
Sign up to set email alerts
|

Artemisinin-Resistant Plasmodium falciparum Parasites Exhibit Altered Patterns of Development in Infected Erythrocytes

Abstract: bArtemisinin derivatives are used in combination with other antimalarial drugs for treatment of multidrug-resistant malaria worldwide. Clinical resistance to artemisinin recently emerged in southeast Asia, yet in vitro phenotypes for discerning mechanism(s) of resistance remain elusive. Here, we describe novel phenotypic resistance traits expressed by artemisinin-resistant Plasmodium falciparum. The resistant parasites exhibit altered patterns of development that result in reduced exposure to drug at the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
120
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(127 citation statements)
references
References 27 publications
7
120
0
Order By: Relevance
“…Drug resistance to widely used artemisinin-based therapies (Carter et al, 2015;Hott et al, 2015) has become an imminent issue since drugresistance strains were identified in Bangladesh, Cambodia, Thailand, Vietnam, Myanmar and Laos (Haque et al, 2013;Na-Bangchang and Karbwang, 2013;Witkowski et al, 2013). Growing global efforts are focusing on finding new cures to combat malaria drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Drug resistance to widely used artemisinin-based therapies (Carter et al, 2015;Hott et al, 2015) has become an imminent issue since drugresistance strains were identified in Bangladesh, Cambodia, Thailand, Vietnam, Myanmar and Laos (Haque et al, 2013;Na-Bangchang and Karbwang, 2013;Witkowski et al, 2013). Growing global efforts are focusing on finding new cures to combat malaria drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Although all stages are susceptible to artemisinin, a small proportion of the least susceptible stages may survive a single pulse of artemisinin in vitro. Figure 1B illustrates some of the findings for Cambodian-origin parasite clones harbouring K13 variants [27]. Most notably, the exquisite susceptibility of wild-type ring-stage trophozoites is ablated by the pfk13 variant, and this fully resistant stage is extended in duration, thus minimising the proportion of the life cycle spent at the more susceptible stages [mature trophozoite (MT) and early schizont (ES)].…”
Section: Variants Of Pfk13 and The Parasite Cell Cycle In Vitromentioning
confidence: 99%
“…There is very good evidence from laboratory studies of P. falciparum isolates grown in culture that artemisinin susceptibility varies greatly across the cell cycle [26,27]. The patterns as currently understood for wild-type parasites are represented in cartoon form in Figure 1A.…”
Section: Variants Of Pfk13 and The Parasite Cell Cycle In Vitromentioning
confidence: 99%
See 2 more Smart Citations